Structural Change and Global Trade. Issue 1 (15th July 2021) - Lewis, Logan T; Monarch, Ryan; Sposi, Michael; Zhang, Jing
Abstract: Services, which are less traded than goods, rose from 55% of world expenditure in 1970 to 75% in 2015. Using a Ricardian trade model incorporating endogenous structural change, we quantify how this substantial shift in consumption has affected trade. Without structural change, we find that the world trade to GDP ratio would be 13 percentage points higher by 2015, about half the boost delivered from declining trade costs. In addition, a world without structural change would have had about 40% greater welfare gains from the trade integration over the past four decades. Absent further reductions in trade costs, ongoing structural change implies that world trade as a share of GDP would eventually decline. Going forward, higher-income countries gain relatively more from reducing services trade costs than from reducing goods trade costs.